Analysis Of the Contribution of Government Building Materials to The Welfare Level of Community Settlement (Case Study at The Office of The Community Empowerment Agency) In Fakfak Regency - Waromi, Agustina; Mastuti, Enggar; Panginan, Markus (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Development is a process of change that takes place consciously, planned and sustainably with the main goal of improving the welfare of human life or the people of a nation. This means that development always moves from an unfavorable condition or living condition to a better life in order to achieve the national goals of a nation. The research method is qualitative. The results of the study show that the housing built in Fakfak Regency as a place of settlement is on average still very simple and still semi-traditional in nature, even quite a lot of which are still traditional. The people of Fakfak Regency build houses only to the extent of their knowledge to build houses as shelters, Conclusion for the Office of Community Empowerment (BPM) to prioritize infrastructure development programs, especially those related to the construction of community housing settlements in order to improve the welfare of the people in Fakfak Regency. For the Regional Government of Fakfak Regency to be more focused on infrastructure development related to the welfare of the community, especially public housing to make it more livable by providing an even larger budget plan for the sector so that the results will be better and more optimal in the context of the welfare of the people of Fakfak Regency.